2005
DOI: 10.1016/j.ydbio.2005.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions coordinating the development of the forebrain and face

Abstract: From an architectural point of view, the forebrain acts as a framework upon which the middle and upper face develops and grows. In addition to serving a structural role, we present evidence that the forebrain is a source of signals that shape the facial skeleton. In this study, we inhibited Sonic hedgehog (Shh) signaling from the neuroectoderm then examined the molecular changes and the skeletal alterations resulting from the treatment. One of the first changes we noted was that the dorsoventral polarity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
277
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(288 citation statements)
references
References 49 publications
9
277
1
1
Order By: Relevance
“…Increased expression of BMP2, BMP4, and BMP7 in the FEZ (Fig. 2R, this study; Hu et al, 2003;Abzhanov et al, 2004;Marcucio et al, 2005;Foppiano et al, 2007) and fading of FGF8 expression from the midfacial ectoderm result in downregulation of TBX22 in the medial part of the face. This mode of TBX22 regulation is supported by the results of NOGGIN bead implantations into the lateral nasal or frontonasal processes, which resulted in preservation of TBX22 expression around the nasal pits and in the midfacial area close to the inductive FGF8 signal.…”
Section: Fgf and Bmp Signaling Pathways Converge On The Regulation Ofmentioning
confidence: 52%
See 1 more Smart Citation
“…Increased expression of BMP2, BMP4, and BMP7 in the FEZ (Fig. 2R, this study; Hu et al, 2003;Abzhanov et al, 2004;Marcucio et al, 2005;Foppiano et al, 2007) and fading of FGF8 expression from the midfacial ectoderm result in downregulation of TBX22 in the medial part of the face. This mode of TBX22 regulation is supported by the results of NOGGIN bead implantations into the lateral nasal or frontonasal processes, which resulted in preservation of TBX22 expression around the nasal pits and in the midfacial area close to the inductive FGF8 signal.…”
Section: Fgf and Bmp Signaling Pathways Converge On The Regulation Ofmentioning
confidence: 52%
“…Later, increased BMP signaling adjacent to the developing nasal pits represses TBX22 in that area and restricts its expression to lateral domains close to the eyes. Around HH20, the frontonasal ectodermal zone (FEZ), a signaling center that controls development of the distal tip of the upper jaw/beak, forms along the oronasal boundary (Hu et al, 2003;Marcucio et al, 2005). Increased expression of BMP2, BMP4, and BMP7 in the FEZ (Fig.…”
Section: Fgf and Bmp Signaling Pathways Converge On The Regulation Ofmentioning
confidence: 99%
“…Examination of the expression patterns of genes involved in the signaling cascades of Bmp, Fgf, RA, and Shh, as well as the loss-and gain-offunction experimental manipulations of these molecules in chicks, generally support their homologous roles (at least at a gross level), suggesting some level of conservation between birds and mammals in their elaboration of jaw development (e.g., Bally-Cuif et al, 1995;Wall and Hogan, 1995;Barlow and Francis-West, 1997;Helms et al, 1997;Hu and Helms, 1999;Sun et al, 2000;Lee et al, 2001;Schneider et al, 2001;Ashique et al, 2002;Mina et al, 2002;Hu et al, 2003;Schneider and Helms, 2003;Song et al, 2004;Tucker and Lumsden, 2004;Wu et al, 2004;Marcucio et al, 2005;Havens et al, 2005). The information gleaned from the many studies of the application or repression of signaling cascades in the facial primordial of chicks highlight an important point regarding the hinge and caps model and jaw development: such studies collectively emphasize the synergy and juxtaposition of combinations of these signaling molecules-in particular in the caps regions and pharyngeal plate-in how such molecules regulate jaw development.…”
Section: Comparing the Components Of "Hinge And Caps" Model Between Taxamentioning
confidence: 91%
“…Shh signaling within the forebrain is required for the induction of Shh in the frontonasal ectodermal zone. 45 To monitor the Shh signaling, we examined the expression of a Shh target gene, Ptch1 (also the Shh receptor). Using either a Shh reporter line, PtcD-lacZ (Ptch1 tm2Mps ), or in situ hybridization with a Shh probe, we found that the Shh response was expanded throughout the prechordal plate of Apaf1 yautja mutant embryos, whereas expression in wild-type embryos was restricted to the ventral-most cells ( Figure 5C and data not shown).…”
Section: Resultsmentioning
confidence: 99%